2021
DOI: 10.1002/ecs2.3442
|View full text |Cite
|
Sign up to set email alerts
|

Annual winter water‐level drawdowns influence physical habitat structure and macrophytes in Massachusetts, USA, lakes

Abstract: Annual wintertime water‐level drawdowns are a common management strategy in recreational lakes; however, few studies have estimated their relative impact on lake littoral habitat among a set of typically co‐occurring anthropogenic stressors including lakeshore development and herbicide application. Within 21 Massachusetts, USA lakes that represented a drawdown magnitude gradient (0.07–2.26 m), we assessed depth‐specific littoral habitat (coarse wood, sediment, macrophytes) at two sites adjacent to forested or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…The data and analysis framework developed for MA can serve as a template for assessing drawdown practices in other parts of the world, which is not feasible with in situ monitoring alone. The ability to detect WD carries many potential management applications, such as evaluating effects on near-shore habitats and relationships to lake water quality [2,35]. The information on drawdown frequency and metrics can aid water managers and policy makers in setting guidelines for balancing the intended benefits of drawdowns for nuisance plant control and infrastructure protection versus the potential ecological impacts of these artificial water-level manipulations [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The data and analysis framework developed for MA can serve as a template for assessing drawdown practices in other parts of the world, which is not feasible with in situ monitoring alone. The ability to detect WD carries many potential management applications, such as evaluating effects on near-shore habitats and relationships to lake water quality [2,35]. The information on drawdown frequency and metrics can aid water managers and policy makers in setting guidelines for balancing the intended benefits of drawdowns for nuisance plant control and infrastructure protection versus the potential ecological impacts of these artificial water-level manipulations [9].…”
Section: Discussionmentioning
confidence: 99%
“…Most WD lakes implement drawdowns in the fall by releasing water downstream when river flows are lowest. Past research indicates that the timing of these drawdowns, which coincide with the region's seasonal precipitation and temperature patterns, can significantly impact physical habitat structure and macrophytes in Massachusetts lakes [35]. The overall methods including data collection, processing, and analysis steps involved to achieve the objectives of this study are shown in Figure 2.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…In order to clearly identify the community composition and spatiotemporal distribution of cladocerans and copepods in a river, it is important to investigate the relationship between these communities and the structure of their microhabitat. As the physical microhabitat structure of freshwater ecosystems mainly depends on aquatic macrophytes [31,32], the abundance of these organisms must also be considered.…”
Section: Introductionmentioning
confidence: 99%